Flexural testing and analysis of full-strain-fields in sandwich composites (Fracture and Structural Integrity, 2019)
The objective of this work was to characterize the full-field flexural behavior of composite sandwich beams. Finite element analysis was used to estimate the behavior of sandwich beams under three- and four-point-bending tests and were compared with experimental results obtained via digital image correlation and strain-gages. Two different core thicknesses and two different sandwich lengths were used to simulate short- and long-beam. Two distinct sandwich beams were fabricated by bonding basalt fiber reinforced polymer composite face sheets (laminates) to polyurethane core and aluminum face sheets glued to polyurethane core with an adhesive film. Full-strain-fields and flexural displacements were obtained by means of strain-gages and digital image correlation technique. Experimental results were in good agreement with predictions and digital image technique attested to be a complementary method to strain-gages in experimental full-strain-fields analysis.
Keywords: Composite sandwich beams; strain-fields; FEM; DIC; VIC; strain-gages